Phenolome of Asian Agrimony Tea (Agrimonia asiatica Juz., Rosaceae): LC-MS Profile, α-Glucosidase Inhibitory Potential and Stability - I. Kashchenko, Nina (Foods, 2020)
Functional beverages constitute the rapidly increasing part of the functional food section and represent an area with a wide range of products including herbal-based beverages. We carried out screening investigations of the extracts of 85 Rosaceous tea plants. Among the extracts analyzed Agrimonia asiatica herb extract demonstrated the highest inhibitory activity against the enzyme α-glucosidase (20.29 µg/mL). As a result of chromato-mass-spectrometric profiling of A. asiatica herb with high-performance liquid chromatography with photodiode array and electrospray triple quadrupole mass-spectrometric detection (HPLC-PDA-ESI-tQ-MS) 60 compounds were identified, including catechins, ellagitannins, flavones, flavonols, gallotannins, hydroxycinnamates, procyanidins, most for the very first time. The analysis of the seasonal variation of metabolites in A. asiatica herb demonstrated that the phenolic content was highest in summer samples and lower in spring and autumn. HPLC activity-based profiling was utilized to identify compounds of A. asiatica herb with the maximal α-glucosidase inhibitory activity. The most pronounced inhibition of α-glucosidase was observed for agrimoniin, while less significant results of inhibition were revealed for ellagic acid and isoquercitrin. The evaluation of phenolic content in A. asiatica herbal teas with the subsequent determination of α-glucosidase inhibiting potential was discovered. Maximum inhibition of α-glucosidase was observed for hot infusion (75.33 µg/mL) and the minimum for 30 min decoction (159.14 µg/mL). Our study demonstrated that A. asiatica herbal tea is a prospective functional beverage in which dietary intake may help to reduce blood glucose.